2016
DOI: 10.1007/s00701-016-2904-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pallidal deep brain stimulation in myoclonus-dystonia: our experience in three cases and their follow-up

Abstract: DBS of bilateral GPi is an effective and safe therapy to be considered in MDS refractory cases. Careful neuropsychological evaluation is essential inside the presurgery planning. Correct location of the DBS electrodes and individualized selection of stimulation parameters in each case are the main determinants of the best clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Improvements in the Unified Myoclonus Rating Scale also improved from 11% to 100% 112. Our patient had a reduction in her BFMDS by 96% with low-frequency, high pulse width pallidal stimulation, similar to two recent cases of MD that responded to 60 Hz pallidal stimulation 13. Unlike these recent cases, however, our case was not positive for the SGCE gene, yet demonstrated a robust reduction in clinical severity, as seen in the reduction of her CGI from 7 to 1.…”
Section: Discussionsupporting
confidence: 80%
“…Improvements in the Unified Myoclonus Rating Scale also improved from 11% to 100% 112. Our patient had a reduction in her BFMDS by 96% with low-frequency, high pulse width pallidal stimulation, similar to two recent cases of MD that responded to 60 Hz pallidal stimulation 13. Unlike these recent cases, however, our case was not positive for the SGCE gene, yet demonstrated a robust reduction in clinical severity, as seen in the reduction of her CGI from 7 to 1.…”
Section: Discussionsupporting
confidence: 80%
“…These results are congruent with our previous short‐term studies and smaller‐cohort long‐term studies . Nevertheless, to our knowledge, the current study represents the longest mean follow‐up in M‐D patients with DBS that has been reported so far (DBS studies including at least 3 patients with M‐D are shown in Table ). Interestingly, we report better improvement in both myoclonus and dystonia than in the previous reports of M‐D and similar or better improvement in dystonia compared with the long‐term follow‐up of larger groups that were clinically and etiologically heterogeneous .…”
Section: Discussionmentioning
confidence: 99%
“…All variables in this group were evaluated in a crosssectional manner. Based on MMSE and daily functioning, all patients had normal cognitive function (mean MMSE, 28.6 ± 1.9; range, [25][26][27][28][29][30] and no frontal lobe dysfunction (mean FAB, 16.6 ± 1.3; range, [15][16][17][18]. With the exception of 1 patient with self-reported depression and anxiety, none of the patients were depressed or anxious (mean BDI-II, 5.7 ± 6.1; range, 0-19; mean HADS-A, 7.7 ± 3.7; range, 2-14; mean HADS-D, 3.3 ± 2.8; range, 0-8).…”
Section: Nonmotor Symptoms and Quality Of Lifementioning
confidence: 99%
“…Valproic acid was found to be ineffective in several studies [43, 51]. In severe medically refractory cases, pallidal (GPi) deep brain stimulation (DBS) should be considered [5256], earlier rather than later [57, 58]. …”
Section: Reviewmentioning
confidence: 99%
“…As a general rule, less invasive modalities such as medications and/or BoNT are usually tried before DBS, although the dramatic response of DYT1 generalized dystonia or DYT11 dystonia to DBS supports early intervention [5261]. The list of indications for DBS in dystonia has been expanding.…”
Section: Reviewmentioning
confidence: 99%